The role of marketing creativity in improving employee performance: An exploratory study of the opinions of a sample of employees at the General Soft Textile Company in Hilla - Rehab Hussein Jawad Al-Kuraiti (Iraqi Journal for Administrative Sciences, 2025)
The role of creativity in improving the performance of marketing staff The study aimed to determine the role of creative marketing to improve the performance of employees and the study was conducted on a sample of workers in the company of the fabric soft in Hilla was the sample (25) factor and represent the study population have been using some statistical tools to test hypotheses of the study The results of the study, no differences morale among employees about the dimensions of creative marketing due to reasons such as culture and the type of activity practiced by the company and found the study to determine the relative importance of each of the dimensions of creative marketing and indicators of the exceptional performance of staff and concluded the study recommendations of the most important, the need to strengthen training and continue it and develop it, and also to strengthen after efficiency as long as was the importance primarily relative to this dimension.